Estudo clínico-epidemiológico, em especial das alterações telerradiográficas do tórax de portadores de paracoccidioidomicose acompanhados no Hospital das Clínicas da Universidade Federal de Minas Gerais de 1976 até 2005. - Ricardo Miguel Costa de Freitas (2006)
The clinical and radiologic pulmonary findings of forty-four patients withparacoccidiodomycosis (PCM) were investigated. The patients were selected from an initial group of 61 patients admitted to the University Hospital of Universidade Federal de Minas Gerais, between 1976 and 2005. Seventeen patients were excluded, either by current orprevious diagnosis of tuberculosis, asthma, chronic obstructive lung disease or pneumoconiosis. In general, they were predominantly males, young-adults, afro-descendents, smokers, and rural workers. The most frequent respiratory manifestations were productive cough and dyspnea. The patients were divided in two groups of 23 and 21 individualsaccording to the presence or absence of chest x-ray abnormalities, respectively, and their clinical signs and symptoms were compared. There were no significant differences between the two groups, as demonstrated by Q-square tests, suggesting clinical-radiologic dissociation. The most frequent radiologic findings were nodular, bilateral and diffuse interstitial infiltrates. Radiologic abnormalities were compared with the current literature, resulting in a simplified classification of radiologic lung PCM findings.